The comparison of aboveground C-stock between cacao-based agroforestry system and cacao monoculture practice in West Sumatra, Indonesia (Biodiversitas Journal of Biological Diversity, 2018)
Santhyami,  Basukriadi A, Patria MP, Abdulhadi R. 2018. The comparison of aboveground C-stock between cacao-based agroforestry system and cacao monoculture practice in West Sumatra, Indonesia. Biodiversitas 19: 472-479. One of the main cause of climate change is deforestation for agricultural purposes. Therefore, Agroforestry System-AFS is regarded as a benign approach to reduce pressure on natural forest while still meeting the needs of local communities. In West Sumatra, Indonesia, small-scale AFS with cacao (Theobroma cacao L.) is the most commonly developed agroforestry system. At present, there is a tendency to intensify cacao-based AFS by reducing the shade trees leading to monoculture practice.  Although many studies had demonstrated the benefits of agroforestry over monoculture, not many studies have been looking at the comparison of carbon stock (C-Stock) of cacao-based AFS with different types of shade trees, particularly in West Sumatra. This study aimed to compare the aboveground C-Stock of three types of cacao-based AFS developed in West Sumatra; (i) Cacao-Rubber (CR), (ii) Cacao Multi-strata (CM), (iii) Cacao-Coconut (CC) with monoculture practice. Using replicated nested plot design, data were collected in April-June 2017 in Pasaman District for CR and CM and Padang Pariaman District for CC and monoculture. Biomass of cacao and shade trees and saplings were determined using allometric equations. The highest total aboveground biomass and C-Stock was found in CC AFS system (an average of 206.84 Mg ha-1 containing 103.42 MgC ha-1, respectively). The lowest total aboveground biomass and C-Stock was found in monoculture system (an average of 20 Mg ha-1 containing 10 MgC ha-1, respectively). Cacao-based AFS in West Sumatra has the potential to contribute to carbon storage by increasing the stocking density of shade tress through carbon-friendly intensification. An additional incentives should be considered such as including the farmers in environmental service reward schemes for maintaining high C stocks in their farms.
Keywords: C-stock; agroforestry; cacao; monoculture; Sumatra